Effect of DyF3 on the corrosion behavior of hot‐pressed Nd–Fe–B permanent magnets. Issue 2 (10th December 2013) - Sueptitz, R.; Sawatzki, S.; Moore, M.; Uhlemann, M.; Gutfleisch, O.; Gebert, A.
<x xml:space="preserve">Abstract</x> The grain boundary diffusion process (GBDP) with DyF3 is a promising method to obtain excellent magnetic properties in Nd–Fe–B permanent magnets. Compared to conventionally prepared (Dy, Nd)–Fe–B magnets the overall content of the precious heavy rare earth Dy is reduced. Thus, the GBDP with DyF3 is highly attractive to cut down costs and save resources. However, it is not well known how the addition of DyF3 affects the corrosion resistance of Nd–Fe–B permanent magnets. In this work, the anodic polarization behavior of hot‐pressed Nd–Fe–B magnets with and without DyF3 additions was investigated in electrolytes of different pH values. The results were compared with measurements on a commercially sintered Nd–Fe–B permanent magnet. In the polarization studies the only observed significant impact of DyF3 additions is an increased passive current density in alkaline media. The pitting susceptibility in NaOH solutions containing chloride ions is not affected by DyF3. Also in contrast to expectations, first free corrosion studies indicated no significant impact of the DyF3 additions on the dissolution rate.